Impact of St. John's wort extract Ze 117 on stress induced changes in the lipidome of PBMC - Hendrik Bussmann; Swen Bremer; Hanns Häberlein; Georg Boonen; Jürgen Drewe; Veronika Butterweck; Sebastian Franken (BMC, 2023)
Abstract Background Membrane lipids have an important function in the brain as they not only provide a physical barrier segregating the inner and outer cellular environments, but are also involved in cell signaling. It has been shown that the lipid composition effects membrane fluidity which affects lateral mobility and activity of membrane-bound receptors. Methods Since changes in cellular membrane properties are considered to play an important role in the development of depression, the effect of St. John's wort extract Ze 117 on plasma membrane fluidity in peripheral blood mononuclear cells (PBMC) was investigated using fluorescence anisotropy measurements. Changes in fatty acid residues in phospholipids after treatment of cortisol-stressed [1 μM] PBMCs with Ze 117 [10-50 µg/ml] were analyzed by mass spectrometry. Results Cortisol increased membrane fluidity significantly by 3%, co-treatment with Ze 117 [50 µg/ml] counteracted this by 4.6%. The increased membrane rigidity by Ze 117 in cortisol-stressed [1 μM] PBMC can be explained by a reduced average number of double bonds and shortened chain length of fatty acid residues in phospholipids, as shown by lipidomics experiments. Conclusion The increase in membrane rigidity after Ze 117 treatment and therefore the ability to normalize membrane structure points to a new mechanism of antidepressant action of the extract.